Influence of Pin Cold Treatment on the Wear Property of Engine Timing Chain - Weng Jianliang; Yin Debing; Qian Jiang; Zhao Jianxiang (Jixie chuandong)
The wear property of pin is the key influence factor on automobile engine timing chain wear,the pin after cold treatment can substantially eliminate residual austenite and the carbide is refined organization,the surface hardness of pin is further improved,it plays a key role for the wear resistance of the part.